Retrieval of a Missing Translocated Intrauterine Contraceptive Device Using Combined Laparoscopic and Cystoscopic Techniques - Shahd T. Natsheh; Mahmoud R. Manasra; Ahmad G. Hammouri; Nour K. Fakhorui; Yazan M. Abugharbieh; Alaa M. I. Alazzeh (Case Reports in Obstetrics and Gynecology, 2024)
Background. Intrauterine contraceptive devices (IUCDs) are considered to be an effective way of preventing unwanted pregnancies. However, one significant complication associated with IUCDs is uterine perforation especially at the time of insertion and could reach the peritoneal cavity and the viscus of the adjacent organs. Intravesical migration is extremely rare. Case Presentation. We report a 41-year-old woman who was diagnosed with IUCD intravesical migration after she presented to our hospital complaining of persistent lower urinary tract symptoms. Laparoscopic removal was done after the failure of cystoscopic extraction. Conclusion. The IUCD must be monitored continuously by the gynaecologist, and suspicions of intravesical migration must be considered in those presenting with persistent, unexplained lower urinary tract symptoms.